HBV integrated genomic characterization revealed hepatocyte genomic alterations in HBV-related hepatocellular carcinomas - Yang, Ming (Mol Clin Oncol, 2020)
Hepatocellular carcinoma (HCC) is one of the most lethal malignancies that is closely associated with the Hepatitis B virus (HBV). HBV integration into host genomes can induce instability and the aberrant expression of human genomic DNA. To directly assess HBV integration breakpoints at whole genome level, four small sequencing libraries were constructed and the HBV integration profiles of four patients with HCC were characterized. In total, the current study identified 11,800,974, 11,216,998, 11,026,546 and 11,607,842 clean reads for patients 1-3 and 4, respectively, of which 92.82, 95.95, 97.21 and 97.29% were properly aligned to the hybrid reference genome. In addition, 220 HBV integration events were detected from the tumor tissues of four patients with HCC and an average of 55 breakpoints per sample was calculated. The results indicated that HBV integration events may be implicated in HCC physiologies and diseases. The results acquired may also provide insight into the pathogenesis of HCC, which may be valuable for future HCC therapy.